Cambios de usos del suelo en el Partido de Luján (1990 - 2010). Elaboración de cartografía temática y análisis espacial con Sistemas de Información Geográfica. - Cantarelo, Clara (2020)
The present Final Degree Project is part of the project "Spatial analysis of urban growth and conflicts in th e face of changes in land use in the Luján river basin (Province of Buenos Aires, Argentina), 1990 - 2010, and its modeling around 2030. Diagnosis and proposals with Geographic Information Systems. First part: elaboration of thematic cartography and detectio n of changes in land uses. ” The topic of this research is entitled “Changes in land uses in the Luján district 1990 - 2000 and 2010 from the elaboration of thematic cartography and spatial analysis with Geographic Information Systems” and its main objective is to carry out a spatial analysis of land use changes in this match. The technical procedures are based on the use of Geographical Information Systems and Remote Sensing for the identification and delimitation of urban spaces. Likewise, satellite images from the Landsat 5 satellite (TM sensor) and images from the Google Earth pro platform were used as a reference base for digitizing vector entities by applying visual interpretation techniques. From this information, it is possible to advance towards the a nalysis of urban expansion in the compact and dispersed modality in order to generate geographic information at the split level of the land use dynamics in the study area. Keywords: Geographic Information Systems, Luján district, urban areas, urban dynamics, compact urban use, dispersed urban use